Development of non-sweetened dehydrated papaya (Carica papaya Linn.) - Sarmiento Evangeline S.
A feasibility study on the development of non-sweetened dehydrated papaya as a healthy snack food was undertaken. Variables such as the degree of maturity of papaya, blanching time, suphite level, and drying temperatures were studied. Objective and sensory results in Phase I showed that the degree of maturity of papaya which best suited the process for dehydration was the 60% green and 40% yellow type. Slices preferred were those of 1/2 centimeter thickness for easy drying and better texture. The levels of the variables chosen to be used for the standardization process were as follows: blanching time at 5 minutes at 97°C, sulfite level at 200 ppm and drying temperature at 55°C to 60°C. Phase II which involved the pilot scale processing of non - sweetened dehydrated papaya was conducted using the variables chosen in Phase I. Four and one half kilograms of papaya were used which yielded 9% of the finished product. Water activity was tested to be 0.58. Cost analysis was also studied to establish the feasibility of producing the product commercially. Phase III involved the addition of artificial fruit flavors for the purpose of increasing product acceptability. Results showed that flavored non- sweetened dehydrated papaya. Cost comparison of the artificially flavored and non-artificially flavored dried papaya was also done. The cost difference was observed to be only P1.20 for the 4.5 kilograms production batch. To be able to sell the product commercially to the right consumers, consumer information using appropriate product labeling is needed to increase consumer awareness and product acceptability.